The Male Reproductive Cycle of the Spotted Toad-Headed Agama, Phrynocephalus maculatus, in Iran - Rahmani, Soheila; Hojati, Vida (International Journal of Zoology, 2015)
The spotted toad-headed agama, Phrynocephalus maculatus, distributed in the central and southeastern arid regions of Iran, belongs to the Agamidae family. In this research, the male reproductive cycle of this species was studied from 5 April to 5 August, 2013. Totally, 40 adult males were collected at midday from southern deserts of Damghan County, located in Semnan Province of Iran. Testes were removed and processed for morphometric and histological studies. The spermatogenic cycle begins from early April, mating occurs in mid-May, and it ends in August. Maximum reproductive activity occurs in early June and reduces from early July and ends in August. The numbers of seminal vesicles were 33–127 and their diameter varied between 69.0 and 258.3 microns. The diameter of tunica albuginea varied between 3.0 and 8.1 microns. The diameter of germinal layer varied between 10.0 and 110.0 microns. There were significant differences in macroscopic and microscopic testicular characters between months. Also, there were no significant differences in the testicular and hemipenal characters between the left side and the right side of body. Since spermatogenesis occurs from April through August, P. maculatus follows an associated reproductive cycle typical for temperate species.